Development of Pyridazinone Chemotypes Targeting the PDEδ Prenyl Binding Site. Issue 25 (3rd November 2016) - Murarka, Sandip; Martín‐Gago, Pablo; Schultz‐Fademrecht, Carsten; Al Saabi, Alaa; Baumann, Matthias; Fansa, Eyad K.; Ismail, Shehab; Nussbaumer, Peter; Wittinghofer, Alfred; Waldmann, Herbert
Abstract: The K‐Ras GTPase is a major target in anticancer drug discovery. However, direct interference with signaling by K‐Ras has not led to clinically useful drugs yet. Correct localization and signaling by farnesylated K‐Ras is regulated by the prenyl binding protein PDEδ. Interfering with binding of PDEδ to K‐Ras by means of small molecules provides a novel opportunity to suppress oncogenic signaling. Here we describe the identification and structure‐guided development of novel K‐Ras–PDEδ inhibitor chemotypes based on pyrrolopyridazinones and pyrazolopyridazinones that bind to the farnesyl binding pocket of PDEδ with low nanomolar affinity. We delineate the structure–property relationship and in vivo pharmacokinetic (PK) and toxicokinetic (Tox) studies for pyrazolopyridazinone‐based K‐Ras–PDEδ inhibitors. These findings may inspire novel drug discovery efforts aimed at the development of drugs targeting oncogenic Ras. Abstract : Reaching deep : The identification and structure‐guided development of novel K‐Ras–PDEδ inhibitor chemotypes based on pyrrolopyridazinones and pyrazolopyridazinones that bind to the farnesyl binding pocket of PDEδ with low nanomolar affinity is described. The results may inspire novel drug‐discovery efforts aimed at the development of drugs targeting oncogenic Ras.